A fruitful endeavor: Smallholders' climate change adaptation strategies through tree species selection for planting - Luisa Müting; Oliver Mußhoff (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2025)
In the African Sahel region, arable land is being increasingly threatened by the implications of climate change. Agroforestry offers opportunities to adapt to these challenges by enhancing ecological resilience and food production through intensification and/or diversification by integrating fertilizer and/or fruit trees. While previous studies have explored agroforestry adoption broadly, little is known about how smallholders' tree species selection aligns with their perceptions of climate change. This study investigates whether Senegalese smallholders plant trees and how they select fertilizer and/or fruit tree species to adapt their food production to perceived climate change effects. Using survey data from 606 smallholders in the Senegalese Groundnut Basin, we grouped reported tree species into fertilizer and fruit tree categories and applied a Heckman regression model for our analysis. Our results show that resource constraints, such as limited access to wells, secure land tenure, agroforestry knowledge, or financial resources are main barriers to tree planting. Climate change perceptions, however, affect species selection, with fruit trees likely being selected when for instance land degradation or shortened rainy seasons are perceived as threats. The perception of soil salinization discourages fertilizer and fruit tree planting. Policy efforts should focus on improving resource access, promoting salt-tolerant tree species, and encouraging smallholders to integrate both, fertilizer and fruit trees into cropping systems to enhance intensification and diversification of food production as holistic adaptation strategy to climate change effects.
Keywords: Q12; Q19; Q23; Q54; 330; Climate change adaptation; Agroforestry; Tree species selection; Land restauration; Smallholders; Sahel